Settlement analysis of the giant open caisson during the construction of the Changtai Yangtze River Bridge - Guo, Mingwei; Dong, Xuechao; Yang, Zhi (Frontiers in Earth Science, 2023)
With the increasing size of open caissons in large-span bridge projects, the overall settlement of giant open caissons is vital to the safe construction of bridge superstructures. Taking the engineering case of the Changtai Yangtze River Bridge, the overall deformation of an open caisson was studied during the construction stage of the bridge’s superstructures. First, the theoretical layer-wise summation method was utilized to analyze the settlement of the open caisson. Then, a 3-D finite element model was established to simulate the installation stage of the bridge superstructure. Finally, a large centrifuge model test was performed to obtain the deformation of the open caisson at each step of bridge’s construction. The results of these approaches demonstrated that final settlements were quite consistent—approximately 225 mm when the bridge superstructure was completely installed—and the settlement deformation curve could be divided into three stages: slowly increasing, rapid, and stabilizing. This study can provide significant guidance for the construction of the Changtai Yangtze River Bridge and be a reference for similar open caisson engineering projects.